Pengembangan Bahan Ajar Ilmu Pengetahuan Alam (IPA) Berbasis Contextual Teaching and Learning (CTL) pada Materi Hubungan Makhluk Hidup dalam Ekosistem di Kelas V - Duwi Putri Zulyanti; Endang Widi Winarni; Abdul Muktadir (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
Based on the results of validator assessments and student responses to teaching materials on the relationship between living things in ecosystems in class V SD Negeri 35 Bengkulu Tengah, this study aims to develop CTL-based Natural Science teaching materials and determine their feasibility. The R&D procedure refers to the Borg and Gall development model, which has ten stages, but only six are used by the researchers, namely up to the use trial and then product revision based on input from the six validators. The study's findings were based on the validator's assessment of the material aspect, which received an average score of 0.86, the language aspect received an average score of 0.86, and the media aspect received an average score of 0.88. The overall average of these three aspects yields a score of 0.87 in the very feasible category, while the results of student responses to the product yield an average score of 80.62 in the very good category. Based on the assessment results, it is possible to conclude that the developed teaching materials in the form of CTL-based printed book are very feasible and suitable for use in the science learning process.